Chronic unpredictable mild stress-induced mouse ovarian insufficiency by interrupting lipid homeostasis in the ovary - Xiang, Yongjie; Jiang, Lin; Gou, Junjie; Sun, Yibo; Zhang, Dongyu; Xin, Xigeng; Song, Zhenhua; Huang, Jiaojiao (Frontiers in Cell and Developmental Biology, 2022)
Ovarian insufficiency results from a number of disorders and a certain causal relationship between psychological stress and ovarian insufficiency has been reported, but the underline mechanism remains unclear. In our study, C57BL/6J female mice were subjected to chronic unpredictable mild stress (CUMS), depression-like mice were selected and identified according to the behavioral tests. The defective ovarian follicle development, low 17-βestradiol (E2) and anti-Mullerian hormone (AMH) levels which were consistent with the clinical characteristics of ovarian insufficiency, indicated that depression-like mice may be used to assess the effects of psychological stress on female reproductive function. To investigate a possible mechanism, lipid homeostasis of ovary was detected using liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis, and the decreased abundance of cholesteryl ester (CE 24:4) was supported to be associated with the downregulated E2. Moreover, granulosa cells did undergo more apoptosis in response to psychological stress, which was caused by downregulated Bcl2 and Bcl2/Bax in granulosa cells. Additionally, the disorder of cell death and growth related pathways in depression- like mice ovaries, was confirmed by RNA-seq analysis. Taken together, this study will provide better understanding of the female reproductive problem under psychological stress.